O conceito de semelhança: uma proposta de ensino - Maciel, Alexsandra Camara (2004)
The aim of this research was to analyse the difficulties dealt with by first form students attending the Brazilian high school system, as well as to check to what extent a teaching sequence using the concept of homothetic integrated with Geometric Optics can favour the learning of the concept of similarity. Our preliminary studies lead us to observe that teaching-learning problems of the concept of similarity relate to some aspects linked to configurations, enough necessary conditions and the context. Basing our study on three hypotheses, we have tried to answer the following question: Can a student who has been introduced to the concept of homothetic with Geometric Optics learn significantly the concept of similarity? . To make our hypotheses valid, we have elaborated and applied a teaching sequence, using as a theoretical approach a Teaching Boar of Geometry by Bernard Parsysz and the Register of Representation and Functioning of a figure by Raymond Duval. After the use of the teaching sequence, we have done a post-test and a qualitative and quantitative analysis leading to discussions, aiming at the validity of our hypotheses and the answering of the questions of the research. We have come to the conclusion that our hypotheses seem pertinent: the development of activities based on situations related to the formation of shadows and images in dark chambers linked to the concept of homothetic allowed us to touch on the concept of similarity in a broad way, working with various similarity in a broad way, working with various types of configurations and the sufficient conditions necessary for the existence of similarity between two figures